Complications in surgery - Mulholland, Michael W.; Doherty, Gerard M. (Philadelphia : Wolters Kluwer/Lippincott Williams & Wilkins, 2011)
"Complications in Surgery is organized to cover both the broad concepts of surgical care and the complications relevant to operations on specific organs. Surgical epidemiology, operative technique, and disease pathophysiology are each essential in contemporary surgical practice; each is emphasized in this new textbook"--Provided by publisher.
part I. Institutional issues -- part II. Management of surgical complications -- part III. Complications of thoracic surgery -- part IV. Complications of vascular surgery -- part V. Complications of gastrointestinal surgery -- part VI. Complications of endocrine and oncologic surgery -- part VII. Complications of transplantation -- part VIII. Complications of pediatric surgery.
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2022. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Surgery -- Complications; Electronic books